Remoção de poluentes e controle quantitativo de águas pluviais através de biorretenções - Pivetta, Glaucia Ghesti (2022)
Bioretention column are widely used to evaluate the performance of these structures in the removal of pollutants, and to investigate different conceptions of filter media to improve their efficiency. However, there is no standard nor a scientific recommendation on adequate diameters of bioretention columns (DBC), or even which are the uncertainties related to the transfer of results between the different scales of the study. In this study, the effect of the diameter of experimental bioretention columns with two types of filter media on the retention and removal of pollutants from stormwater runoff was evaluated. Bioretention columns with diameters of 400 mm, 300mm and 200mm were submitted to a synthetic stormwater dosage regime and experimentally evaluated to water retention and pollutants removal (TSS, nitrite, nitrate and phosphate). Two types of media filter were used, a conventional (gravel, sand and local soil) and a modified filter media (gravel, sand, local soil and sugarcane bagasse). The results showed that the runoff retention was not affected by the DBC, but yes by the time interval between stormwater dosages. Bioretention with conventional media were slightly more efficient in the runoff retention (34.8%) compared to those with modified media (33.8%). Both types of filter media increased the values of pH and electrical conductivity of the stormwater. Color and turbidity parameters decreased in the media with sugarcane bagasse (33.6% and 50%, respectively), and increased in the conventional media (56% and 9.1%, respectively). The removal of TSS (98%), nitrite (98%) and phosphate (94%) showed no variability among different medias and diameters. Nitrate removal was influenced by the filter media and, mainly, among the DCB. Nitrate exports (-116%) were observed in the bioretention columns with conventional filter media with 400 mm of diameter, as well as the columns with sugarcane bagasse (-94.7%). Bioretention with sugarcane bagasse removed less nitrate in the columns with 300 mm (6%) and 200 mm (32.2%) compared with the columns with conventional filter media (89% and 93%, respectively). The addition of sugarcane bagasse in the filter media contributed to the leaching of nitrate and to the rapid saturation of the filter media, affecting their efficiency in removing pollutants and retention of stormwater. About the pollutants evaluated, the scale effect of the bioretention columns was verified on the performance of nitrate removal, and in bioretention with modified filter media with sugarcane bagasse.